Integrative Management of Darunaka: Insights from a Case Study (AYUSHDHARA, 2025)
Darunaka is a one out of 9 Kapalagata roga affecting the Shiro twaka (scalp) and Kesha (hair). According to Acharya Sushruta, the disease is a Kshudra roga because it is caused by the vitiation of the Vata and Kapha Doshas. The signs and symptoms include Twak sphutana (scratching or breaking of the scalp skin), Rukshata (roughness or dryness of the scalp), Swapa (abnormalities of touch sensation on the scalp), and Kandu (itchiness on the scalp). Darunaka can be compared with dandruff in contemporary science. The disease is mainly concerned with hair root and it is commonly encountered in a clinical practice. It is significantly more common in men and may commence at any time after puberty. Maintenance of proper hygiene is the most important thing in this disease. Otherwise, the chances of recurrence are more. There is at present no viable therapy for this bothersome condition in dermatological practice. As a result, a lot of patients feel hopeful about Ayurveda. We can provide good results in this situation with Ayurvedic medicines. Case Report: A 18 year old female patient from Vadodara came to OPD of Shalakya Tantra, SAMCH, Vadodara with chief complaint of Shirotwaka Sphutanam or Keshabhumi Prapatana (cracking of the scalp skin with fine flakes), Shirah Kandu (itching on scalp), Rukshata (dryness on scalp), Keshachyuti (hair fall) diagnosed with Darunaka was treated with Ayurved Chikitsa. At the same time, the combined benefits of Sthanika Chikitsa and Shamana Aushadhis were advocated. Assessments: The therapy's efficacy was evaluated by comparing signs and symptoms before and after treatment. A unique scoring pattern was created to examine signs and symptoms. Conclusion: The medicine was shown to be both safe and effective in treating signs and symptoms while also enhancing general scalp health.